A human homolog of the Saccharomyces cerevisiae REV3 gene, which encodes the catalytic subunit of DNA polymerase ζ - Gibbs, Peter E. M. (The National Academy of Sciences, 1998)
To get a better understanding of mutagenic mechanisms in humans, we have cloned and sequenced the human homolog of the Saccharomyces cerevisiae REV3 gene. The yeast gene encodes the catalytic subunit of DNA polymerase ζ, a nonessential enzyme that is thought to carry out translesion replication and is responsible for virtually all DNA damage-induced mutagenesis and the majority of spontaneous mutagenesis. The human gene encodes an expected protein of 3,130 residues, about twice the size of the yeast protein (1,504 aa). The two proteins are 29% identical in an amino-terminal region of ≈340 residues, 39% identical in a carboxyl-terminal region of ≈850 residues, and 29% identical in a 55-residue region in the middle of the two genes. The sequence of the expected protein strongly predicts that it is the catalytic subunit of a DNA polymerase of the pol ζ type; the carboxyl-terminal domain possesses, in the right order, the six motifs characteristic of eukaryotic DNA polymerases, most closely resembles yeast pol ζ among all polymerases in the GenBank database, and is different from the human α, δ, and ɛ enzymes. Human cells expressing high levels of an hsREV3 antisense RNA fragment grow normally, but show little or no UV-induced mutagenesis and are slightly more sensitive to killing by UV. The human gene therefore appears to carry out a function similar to that of its yeast counterpart.